Terapi Suportif Terhadap Penurunan Tingkat Kecemasan Keluarga Merawat Anak Retardasi Mental - Isti Harkomah; Sutinah; Nofrida Saswati (Ilin Institute, 2021)
The purpose of this activity is to reduce the level of anxiety felt by families with mentally retarded children by providing supportive therapy. The method of implementing activities is by providing health education, giving leaflets, relaxing deep breaths, and giving therapy. The activity was carried out the Hall of the Lotus Home, Jambi City, with 27 families participating. The analysis technique uses descriptive categorical. The results of the majority of families who have mentally retarded children. Conclusion, families are able to carry out interventions related to reducing family anxiety in treating children with mental retardation by providing supportive therapy.